KELAS WIRAUSAHA PELAJAR: INKUBASI PRODUK LOKAL DAN MARKET DAY SEKOLAH UNTUK MENDUKUNG UMKM DESA BANTARAGUNG, MAJALENGKA JAWA BARAT - Eko Gumaya Sari; Taufan Gojali; Tarto Tarto; Dhea Zatira (POLITEKNIK LP3I JAKARTA, 2026)
The Community Service Program entitled “Student Entrepreneurship Class: Local Product Incubation and School Market Day to Support MSMEs in Bantaragung Village, Majalengka, West Java” is an initiative aimed at enhancing students’ entrepreneurial spirit while supporting the development of local MSME products in the village. This program is motivated by the low involvement of young people in local economic development, as well as the limited promotion and innovation of MSME products within the village environment. The activities are carried out through several stages, namely program socialization, entrepreneurship training, local product incubation assistance, branding and basic marketing training, and the implementation of a school market day as a business practice platform for students. The target participants of this program include junior high school and senior high school/vocational school students, MSME actors, and schools in Bantaragung Village. The methods used in this program are educational and participatory approaches through lectures, discussions, hands-on practice, marketing simulations, and mentoring. Through this activity, students are expected to improve their creativity, communication skills, marketing abilities, and practical entrepreneurial experience. In addition, this program is also expected to help promote local village products, strengthen collaboration among schools, universities, and the community, and support economic growth based on local potential. The expected outcomes of this program include the establishment of student entrepreneurship groups, increased entrepreneurial interest among the younger generation, the development of local product innovation, and the sustainable implementation of school market days as a promotional platform for MSME products from Bantaragung Village.